Democratic Republic of Timor-Leste : 2017 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Timor-Leste's non-oil real GDP growth in 2016 is estimated at 5.5 percent, supported by a near doubling of government capital spending, albeit with large import leakages. Real total GDP declined by 7.9 percent in 2016, owing to a sharp fall in oil production. The overall fiscal deficit widened to 30.8 percent of GDP in 2016. Non-oil real GDP growth is projected to moderate to 3 percent in 2017, owing to lower government expenditure and the slowdown of activity owing to the delayed formation of the new government after the parliamentary elections in July. Inflationary pressures remain low, albeit with a return to positive territory with rising global food and fuel prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet